How Quasar Feedback May Shape the Co-evolutionary Paths - Ishibashi, Wako (Frontiers in Astronomy and Space Sciences, 2017)
Observations point towards some form of "co-evolutionary sequence", from dust-enshrouded starbursts to luminous unobscured quasars. Active galactic nucleus (AGN) feedback is generally invoked to expel the obscuring dusty gas in a blow-out event, eventually revealing the hidden central quasar. However, the physical mechanism driving AGN feedback, either due to winds or radiation, remains uncertain and is still a source of much debate. We consider quasar feedback, based on radiation pressure on dust, which directly acts on the obscuring dusty gas. We show that AGN radiative feedback is capable of efficiently removing the obscuring cocoon, and driving powerful outflows on galactic scales, consistent with recent observations. I will discuss how such quasar feedback may provide a natural physical interpretation of the observed evolutionary path, and the physical implications in the broader context of black hole-host galaxy co-evolution.